Maternal Hypoxia Increases the Excitability of Neurons in the Entorhinal Cortex and Dorsal Hippocampus of Rat Offspring - Amakhin, Dmitry V.; Soboleva, Elena B.; Postnikova, Tatiana Yu.; Tumanova, Natalia L.; Dubrovskaya, Nadezhda M.; Kalinina, Daria S.; Vasilev, Dmitrii S.; Zaitsev, Aleksey V. (Frontiers in Neuroscience, 2022)
Prenatal hypoxia is a widespread condition that causes various disturbances in later life, including aberrant central nervous system development, abnormalities in EEG rhythms, and susceptibility to seizures. Hypoxia in rats on the 14th day of embryogenesis (E14) disrupts cortical neuroblast radial migration, mainly affecting the progenitors of cortical glutamatergic neurons but not GABAergic interneurons or hippocampal neurons. Thus, hypoxia at this time point might affect the development of the neocortex to a greater extent than the hippocampus. In the present study, we investigated the long-term effects of hypoxia on the properties of the pyramidal neurons in the hippocampus and entorhinal cortex (EC) in 3-week-old rats subjected to hypoxia on E14. We observed a reduction in the total number of NeuN-positive neurons in EC but not in the CA1 field of the hippocampus, indicating an increased cell loss in EC. However, the principal neuron electrophysiological characteristics were altered in the EC and hippocampus of animals exposed to hypoxia. The whole-cell patch-clamp recordings revealed a similar increase in input resistance in neurons from the hippocampus and EC. However, the resting membrane potential was increased in the EC neurons only. The recordings of field postsynaptic potentials (fPSPs) in the CA1 hippocampal area showed that both the threshold currents inducing fPSPs and population spikes were lower in hypoxic animals compared to age-matched controls. Using the dosed electroshock paradigm, we found that seizure thresholds were lower in the hypoxic group. Thus, the obtained results suggest that maternal hypoxia during the generation of the pyramidal cortical neurons leads to the increased excitability of neuronal circuitries in the brain of young rats. The increased excitability can be attributed to the changes in intrinsic neuronal properties.